Restaurant business trends - Varkhol, Veronika; Stukalska (Ivanova), Nataliia (My University, 2021)
A whole field is now unfolding on the market, where restaurateurs hone the art of seducing guests and their skills of charisma in order to maximize the attention of the visitor. Therefore, a large number of various modern trends appear in restaurant enterprises. The paper analyzes new trends and concepts being introduced in the establishments of the restaurant industry. New concepts and trends in the restaurant business will help attract new guests, retain regular customers, increase the average check per guest, stay afloat and achieve success.
Keywords: ресторанне господарство; тренди; QR-код; концепції; estaurant industry; trends; QR code; concepts; кафедра технології ресторанної і аюрведичної продукції